Molecular Mechanism for PACAP 38-Induced Neurite Outgrowth in PC12 Cells - Junko Shibato; Fumiko Takenoya; Takahiro Hirabayashi; Ai Kimura; Michio Yamashita; Ichiro Takasaki; Randeep Rakwal; Seiji Shioda (Neural Plasticity)
The present research investigates the molecular mechanism of neurite outgrowth (protrusion elongation) under pituitary adenylate cyclase-activating polypeptide (PACAP) 38 treatments using a rat adrenal-derived pheochromocytoma cell line—PC12. This study specifically looks into the regulation of PACAP38-induced collapsing response mediator protein 2 (CRMP2) previously identified in a mouse brain ischemia model and which could be recovered by PACAP38 treatment. Previously, DNA microarray analysis revealed that PACAP 38-mediated neuroprotection involved not only CRMP2 but also pathways related to glycogen synthase kinase-3β (GSK-3β) and other signaling components. Thus, to clarify whether CRMP2 acts directly on PACAP38 or through GSK-3β as part of the mechanism of PACAP38-induced neurite outgrowth, we observed neurite outgrowth in the presence of GSK-3β inhibitors and activators. PC12 cells were treated with PACAP38 being added to the cell culture medium at concentrations of 10−7 M, 10−8 M, and 10−9 M. Post PACAP38 treatment, immunostaining was used to confirm protrusion elongation of the PC12 cells, while RT-PCR, two-dimensional gel electrophoresis in conjunction with Western blotting, and inhibition experiments were performed to confirm the expression of the PACAP gene, its receptors, and downstream signaling components. Our data show that neurite protrusion elongation by PACAP38 (10−7 M) in PC12 cells is mediated through the PAC1-R receptor as demonstrated by its suppression by a specific inhibitor PA-8. Inhibitor experiments suggested that PACAP38-triggered neurite protrusion follows a GSK-3β-regulated pathway, where the AKT and cAMP/ERK pathways are involved and where the inhibition of Rho/Roc could enhance neurite protrusion under PACAP38 stimulation. Although we could not yet confirm the exact role and position of CRMP2 in PACAP38-mediated PC12 cell elongation, it appears that its phosphorylation and dephosphorylation have a correlation with the neurite protrusion elongation through the interplay of CDK5, which needs to be investigated further.